Investigating the Dark Sector with New Liht and HiddenParticles - Foguel, Ana Luisa (Cadernos de Astronomia, 2026)
Despite its success, the Standard Model (SM) of particle physics remains incomplete, with the absence of a dark matter (DM) candidate being one of its primary gaps. The lack of evidence for new heavy particles has driven interest toward light, feebly interacting DM candidates, whose thermal production in the early Universe requires a portal mediator. In this work, we propose a model where a vector mediator, originating from a U(1)Q gauge symmetry, connects the visible sector to inelastic dark matter (iDM) candidates. Unlike the standard dark photon scenario, in which SM fermions do not carry direct charges under the new symmetry, we explore Q charges defined by combinations of baryonic and leptonic numbers. We demonstrate that this framework can alter the relic abundance calculation and the experimental phenomenology. Consequently, such models can unlock new windows in the parameter space, expanding the possibilities for DM discovery beyond the constraints of the conventional model.